2018
DOI: 10.30516/bilgesci.369068
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Shallow Groundwater Wells In An Agricultural And Coastal Area In Göksu Delta, Turkey

Abstract: The Göksu Delta of Turkey is an alluvial delta with intense agricultural activity and has great ecological and economic significance. The delta is environmental protection area in term of remarkable in natural life. In particular, water birds are an important point, delta chosen as Ramsar site. So, this special area is important in terms of monitoring water quality and effects of anthropogenic activities (such as agricultural). Water samples were collected monthly from 24 wells in the study area, and 13 water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…It has a particular reputation for being one of the few remaining areas in the world where sea turtles lay their eggs. In this area, there are significant and intense agricultural activities each month of the year, due to the typical Mediterranean climate of hot and dry summers, and cool and rainy winters [35]. This area is also located on one of the world's important bird migration routes, and especially in cold winter conditions, when the lakes in Central Anatolia freeze, it provides shelter for bird communities of huge numbers [35].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has a particular reputation for being one of the few remaining areas in the world where sea turtles lay their eggs. In this area, there are significant and intense agricultural activities each month of the year, due to the typical Mediterranean climate of hot and dry summers, and cool and rainy winters [35]. This area is also located on one of the world's important bird migration routes, and especially in cold winter conditions, when the lakes in Central Anatolia freeze, it provides shelter for bird communities of huge numbers [35].…”
Section: Resultsmentioning
confidence: 99%
“…In this area, there are significant and intense agricultural activities each month of the year, due to the typical Mediterranean climate of hot and dry summers, and cool and rainy winters [35]. This area is also located on one of the world's important bird migration routes, and especially in cold winter conditions, when the lakes in Central Anatolia freeze, it provides shelter for bird communities of huge numbers [35]. Several small lakes in the delta, usually less than 1 m deep, with limited areas having about 2 m depth, have abundant aquatic vegetation [9].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Majority of people living in rural areas and making their living from agriculture and animal husbandry meet their irrigation and drinking water needs from groundwater to a large extent, while many of those groundwater resources are inappropriate for drinking. Results of a study (Güner et al 2018) showed that nitrate concentration in 74% of 34 wells across Hacıbektaş Region of Nevşehir was over upper limit for drinking water and that 12% of them had NO 3 concentrations over 100 mg L-1; the water from the wells are consumed for drinking by local people and domestic animals. Güner et al (2018) pointed out that high nitrate levels in the drinking water caused a signi cant decrease in serum LDH and ALP enzyme activities in Akkaraman sheep in the region and serum triglyceride and cholesterol levels of those high nitrate-exposed sheep were signi cantly lower than those unexposed ones.…”
Section: Nitrates In Drinking Watersmentioning
confidence: 99%